Software in the context of luminescence dating: status, concepts and suggestions exemplified by the R package ‘Luminescence’ - Kreutzer, Sebastian; Burow, Christoph; Dietze, Michael; Fuchs, Margret C.; Fischer, Manfred; Schmidt, Christoph (Ancient TL, 2017)
The relevance of luminescence dating is reflected by the steadily growing quantity of published data. At the same time, the amount of data available for analysis has increased due to technological and methodological advances. Routinely, luminescence data are analysed using a mixture of commercially available software, self-written tools and specific solutions. Based on a luminescence dating literature screening we show how rarely articles report on the software used for the data analysis and we discuss potential problems arising from this. We explore the growing importance of the statistical programming language R in general and especially its reflection in recent software developments in the context of luminescence dating. Specifically, for the R package ‘Luminescence’ we show how the transparency, flexibility and reliability of tools used for the data analysis have been improved. We finally advocate for more transparency if unvalidated software solutions are used and we emphasise that more attention should be paid to the tools used for analysing the data.
Gesehen am 27.03.2025